Control of RNA synthesis in Escherichia coli after a shift to higher temperature. - Ryals, J (1982)
Parameters of RNA synthesis were measured after a temperature upshift in a pair of Escherichia coli B/r strains that are isogenic except for having relA and relA+ loci, to examine the cause for a reported anomaly in the correlation between guanosine tetraphosphate (ppGpp) and stable RNA (rRNA, tRNA) synthesis under such conditions. Two main results were: (i) the specific stable RNA gene activity (stable RNA per total RNA synthesis) correlated in the conventionally expected fashion with the level of ppGpp but was obscured by a nonspecific increase in the RNA chain elongation rate due to the higher temperature; (ii) the temperature upshift caused a transient reduction in the RNA polymerase activity (transcribing per total enzyme) that accounts for the previously observed oscillating RNA synthesis rate after a temperature shift.